A DESCRIPTIVE CONTENT ANALYSIS OF THE TEXTBOOK USED OF ENGLISH FOR SPECIFIC PURPOSE - Defy Gustianing; , Prasetyawan Aji Sugiharto; Zulfa Diana Romadhona (Aisyah Journal of English Language Teaching (AIJELT), 2023)
In English foreign language situations, students rarely have chances to use English outside the classroom, consequently English textbook seems to be the only source by which students receive input and the main material for both teachers and students to rely on as well. Every teacher and student needs textbooks to support their teaching and learning process. A textbook is best seen as a source for achieving aims and objectives that have already been set in terms of learners’ needs. English for a specific purpose (ESP) program is therefore built on an assessment of purposes, needs, and the functions for which English is required. As a matter of fact, ESP assesses needs and integrates motivation, subject matter, and content for the teaching of relevant skills. The objective of the study is (1) to comprehend the term of textbooks, (2) to excavate the growth and definition of English for specific purposes and (3) to comprehend the textbook of English for specific purposes. The criteria lists of textbook authors have to be an expert, they have to give examples that relate to the student’s own experiences. The list of activities to be carried out the aims which providing criteria, guidelines, and recommendations. In conclusion, the Textbook of English for specific purposes the most important aspect for teachers to try to engage students with the content they are going to be dealing with. In this case, the authors could take the example of the book, entitled “English for Careers, Tourism 2” by Robin Walker and Keith Harding to make the explanation clearly.